The frailty syndrome and mortality among very old patients with symptomatic severe aortic stenosis under different treatments. (1st December 2016) - Rodríguez-Pascual, Carlos; Paredes-Galán, Emilio; Ferrero-Martínez, Ana Isabel; Baz-Alonso, José Antonio; Durán-Muñoz, Darío; González-Babarro, Eva; Sanmartín, Marcelo; Parajes, Teresa; Torres-Torres, Ivett; Piñón-Esteban, Miguel; Calvo-Iglesias, Francisco; Olcoz-Chiva, Maria Teresa; et al.
Abstract: Background: The role of frailty as a prognostic factor in non-selected patients with symptomatic severe aortic stenosis (SAS) is still uncertain. This study aims to examine the association between the frailty syndrome and mortality among very old patients with symptomatic SAS, and to assess whether the association varies with the type of SAS treatment. Methods and results: Prospective study of 606 patients aged ≥ 75 years with symptomatic SAS, recruited from February 2010 to January 2015, who were followed up through June 2015. At baseline, frailty was defined as having at least three of the following five criteria: muscle weakness, slow gait speed, low physical activity, exhaustion, and unintentional weight loss. Statistical analyses were performed with multivariate Cox regression. At baseline, 49.3% patients were frail. During a mean follow-up of 98 weeks, 35.3% of patients died. The hazard ratio (95% confidence interval) of mortality among frail versus non-frail patients was 1.83 (1.33–2.51). The corresponding results were 1.58 (1.09–2.28) among patients under medical treatment, 3.06 (1.25–7.50) in those with transcatheter aortic valve replacement, and 1.97 (0.83–4.67) in those with surgical aortic valve replacement, p for interaction = 0.21. When the frailty criteria were considered separately, mortality was also higher among patients with slow gait speed [1.52 (1.05–2.19)] or low physical activity [1.35 (1.00–1.85)]. Conclusions: Frailty is associated with increased mortality among patients with symptomatic SAS, and this association does not vary with the type of SAS treatment. Future studies evaluating the benefits of different treatments in SAS patients should account for baseline frailty.